Using social media in communication processes in commercial office properties - Szkop, Katarzyna (Wykorzystanie mediów społecznościowych w procesach komunikacji w komercyjnych nieruchomościach biurowych, 2020)
Intangible factors increasingly contribute to building a sustainable competitive advantage for the company. Turbulent environment of the organization and the rapid development of new technologies, affect the change of behaviour of customers and organizations, contributing to the evolution of the way the company communicates with customers. The growing awareness of customer service standards and their expectation, force a permanent process of adjusting the product offer to the individual needs of the purchaser, and a constant dialogue between the organization and the customer, make it important to gain knowledge and exchange information. The aim of the article is to analyse the possibility of using social media in communication with tenants in commercial office properties. Selected channels of communication with clients were discussed. The research uses the case study method. It is proposed to implement measures that could contribute to the wider use of social media in tenants’ communication with landlords
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 2 (56), s. 52-62
Keywords: social media; communications; commercial office properties; media społecznościowe; komunikacja; komercyjne nieruchomości biurowe